Al-Fikru Al-Dini Fi Masyrui Muassasati Mu'minuna Bila Hududin: Qiroati Nadqoiyati - Mohamed, Hirreche Baghdad (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
The religious phenomenon becomes a subject of reflection from the moment it is practiced by human beings, because it must be understood, explained and interpreted ... The revelation, the rituals and the teachings ... are fixed in sacred texts , these are the object of conservation, reading and questioning. And because the contexts in which they evolve and develop are historical, this constantly poses the modalities of harmonization and application of the texts and the way of living the faith in the present without completely breaking with the faith of the first founders, which leads to